Biphasic effect of hydrogen peroxide on skeletal muscle arteriolar tone via activation of endothelial and smooth muscle signaling pathways. - Cseko, C; Bagi, Z; Koller, A (2004)
We hypothesized that hydrogen peroxide (H2O2) has a role in the local regulation of skeletal muscle blood flow, thus significantly affecting the myogenic tone of arterioles. In our study, we investigated the effects of exogenous H2O2 on the diameter of isolated, pressurized (at 80 mmHg) rat gracilis skeletal muscle arterioles (diameter of approximately 150 microm). Lower concentrations of H2O2 (10(-6)-3 x 10(-5) M) elicited constrictions, whereas higher concentrations of H2O2 (6 x 10(-5)-3 x 10(-4) M), after initial constrictions, caused dilations of arterioles (at 10(-4) M H2O2, -19 +/- 1% constriction and 66 +/- 4% dilation). Endothelium removal reduced both constrictions (to -10 +/- 1%) and dilations (to 33 +/- 3%) due to H2O2. Constrictions due to H2O2 were completely abolished by indomethacin and the prostaglandin H2/thromboxane A2 (PGH2/TxA2) receptor antagonist SQ-29548. Dilations due to H2O2 were significantly reduced by inhibition of nitric oxide synthase (to 38 +/- 7%) but were unaffected by clotrimazole or sulfaphenazole (inhibitors of cytochrome P-450 enzymes), indomethacin, or SQ-29548. In endothelium-denuded arterioles, clotrimazole had no effect, whereas H2O2-induced dilations were significantly reduced by charybdotoxin plus apamin, inhibitors of Ca(2+)-activated K+ channels (to 24 +/- 3%), the selective blocker of ATP-sensitive K+ channels glybenclamide (to 14 +/- 2%), and the nonselective K(+)-channel inhibitor tetrabutylammonium (to -1 +/- 1%). Thus exogenous administration of H2O2 elicits 1) release of PGH2/TxA2 from both endothelium and smooth muscle, 2) release of nitric oxide from the endothelium, and 3) activation of K+ channels, such as Ca(2+)-activated and ATP-sensitive K+ channels in the smooth muscle resulting in biphasic changes of arteriolar diameter. Because H2O2 at low micromolar concentrations activates several intrinsic mechanisms, we suggest that H2O2 contributes to the local regulation of skeletal muscle blood flow in various physiological and pathophysiological conditions.